Implication of Regional Split in Local Government Efficiency: Evidence From North Sumatra, Indonesia - Roosemarina Anggraini Rambe (Jurnal Ekonomi dan Studi Pembangunan, 2020)
The purposes of this study are to (1) measure the level of the relative efficiency of educational spending in achieving the years of schooling at local governments in North Sumatra Province, (2) Compare the relative efficiency level of per capita educational spending between the parent local government and the local governments resulting from the split. The analytical method used is Data Envelopment Analysis with an output-oriented model. The approach used is a variable return to scale. In measuring efficiency, the input used is educational spending per capita, while the output used is the years of schooling. The results showed that the average level of the relative efficiency of 33 local governments in North Sumatra decreased from 2015 to 2018. In 2015, there were three relatively efficient local governments: Medan, Pematang Siantar, and Labuhan Batu. However, in 2018, only Medan is relatively efficient. The efficiency level of Labuhan Batu declined in 2018. In fact, all parent local governments and local governments resulting from split experienced a decrease inefficiency. Thus, a regional split has not succeeded in increasing the relative efficiency of local governments in North Sumatra Province.